ISIS' propaganda machine: global mediated terrorism - Al-Rawi, Ahmed K. (Routledge Focus, 2024)
"This book examines ISIS's media propaganda machine. The book focuses on case studies that have been largely under-studied in relation to ISIS's media production. Empirically, it offers new insights into how ISIS uses its media production to disseminate its extremist ideology by focusing on video games, educational apps, Dark Web sites, and offline billboards. The book argues that despite all the discussion about how ISIS has disappeared or even died, the terrorist group's daily activities on the Dark Web show that they are still thriving and disseminating their propaganda in more than 20 different languages, and effectively functioning as an international news organization. Using a mixed method research approach, the book offers a multilayered understanding of media content and fills a major gap in the literature, especially in relation to the use of educational apps and the Dark Web. This book will be of much interest to students of media and communication studies, terrorism and counter-terrorism, Middle Eastern politics and International Relations."